Does the Abundance of Natural Resources Crowd-Out the Manufacturing Sector? Evidence from Nigeria - Chile, Nzeh Innocent; Uzoechina, Benedict I; Eze, Millicent Adanne; Imoagwu, Chika P; Anyachebelu, Uzoma M. (Asian Development Policy Review, 2021)
Our objective in this study is to investigate if natural resource abundance can crowed-out the manufacturing sector in Nigeria. Under the framework of an ARDL and over a period of 1990-2019, findings of the results showed that in the short-run, natural resources positively impact on the manufacturing value added in the current period; however, after a one period lag, the contribution of natural resources to the manufacturing value added becomes negative. We also found that in the short-run, real interest rate, inflation rate and trade openness are negatively linked to the manufacturing value added, while employment in industry and gross fixed capital formation are positively related to the manufacturing value added. In the long-run, natural resources contributed positively to the manufacturing value added. The long-run results also show that the gross fixed capital formation and inflation rate negatively impact on the manufacturing valued added. The implication of our finding is that natural resources rent is closely linked to the success of the manufacturing sector and as such can also crowd-out the manufacturing sector. On grounds of these findings, we recommend, among others; that the proceeds from natural resources should be used to build critical infrastructure necessary to improve the performance of the manufacturing sector. This way, the economy can be diversified to create the needed employment.